DEVELOPMENT OF NEEDLELESS ELECTROSPINNING FOR THE FABRICATION OF POLYVINYLPYRROLIDONE (PVP)/ CELLULOSE ACETATE (CA)/KAFFIR LIME LEAF EXTRACT NANOCOMPOSITE FIBERS AS AN ANTIBACTERIAL AGENT - Haryanto Agung, Bertolomeus
In this research, a needleless electrospinning system has been developed using A-shape and V-shape spinnerets for mass production of Nanofibers. The spinneret is made of copper metal and aluminium metal and is shaped like the letters A and V with the top end of the spinneret made wide to help the solution form a meniscus (curvature) on the surface. The width of the spinneret surface gap is varied 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm for each type of spinneret. PVP solution was used as a precursor with various concentrations of 8 wt%, 10 wt%, and 12 wt%. Measurements of working stress, production speed, average fiber diameter were then carried out for each type of spinneret. A 1 mm A-type spinneret was then selected for optimization of the spinning process parameters using the Box-Behnken experimental design. Based on the graph of the effect of slit width on working voltage, A-type spinneret requires a relatively lower working voltage with a working voltage of 18.5 kV-24 kV while the V-type spinneret requires a working voltage of 18.9 kV-23 kV. The results of the measurement of the production speed show that the V-type spinneret can produce 11.59 mg/minute of fiber on average, while the A-type spinneret can produce 17.67 mg/minute of fiber. The average fiber diameter produced by A-type spinnerets is 1301 nm with variations in slit width. While the V-type spinneret produces an average fiber diameter of 1598 nm with variations in the spinneret slit width. The results of optimization on spinneret A-type 1 mm show that concentration is a significant factor affecting fiber size. Based on the optimization results, the minimum fiber diameter is obtained at a concentration of 8 wt%, a voltage of 40 kV, and a collector distance of 15 cm. As an application of a needleless electrospinning system (1 mm A-type spinneret), PVP/SA/EDJP composite fibers have been successfully fabricated with PVP/SA:EDJP mass ratio variations of 20:0, 20:1, 20:2, and 20:3. The fiber diameters obtained ranged from (219±8) nm (339±9) nm at a voltage of 40 kV, collector distance of 15 cm, and humidity of 40% Rh. FTIR analysis showed that the absorption peaks in the EDJP solution were also found in the PVP/CA/EDJP absorption spectrum which indicated that the EDJP sample was successfully encapsulated into PVP/SA polymer. The resulting fiber pH ranged from (4.03±0.05) - (4.43±0.05). The inhibition ratio of PVP/CA/EDJP composite fibers to S. aureus bacteria increased with increasing EDJP mass. The minimum inhibition ratio value was 127.26 ±3.31 %/gram and the maximum value obtained from PVP/CA:EDJP 20:3 composite fiber was 448.92 ± 15.07 %/gram.